The Political Economy of National Climate Funds - Bhandary, Rishikesh. (Tufts University. Tisch Library., 2021)
Thesis (Ph.D.)--Tufts University, 2020.; Submitted to the Dept. of Diplomacy, History, and Politics.; Advisor: Kelly Gallagher.; Committee: Dan Drezner, and David Victor.; Keywords: Climate change, and International relations.